The role of air pollution (PM and NO2) in COVID-19 spread and lethality: a systematic review (2020)
A new coronavirus (SARS-CoV-2) has determined a pneumonia outbreak in China (Wuhan, Hubei Province) in December 2019, called COVID-19 disease. In addition to the person-to person transmission dynamic of the novel respiratory virus, it has been recently studied the role of environmental factors in accelerate SARS-CoV-2 spread and its lethality. The time being, air pollution has been identified as the largest environmental cause of disease and premature death in the world. It affects body's immunity, making people more vulnerable to pathogens. The hypothesis that air pollution, resulting from a combination of factors such as meteorological data, level of industrialization as well as regional topography, can acts both as a carrier of the infection and as a worsening factor of the health impact of COVID-19 disease, has been raised recently. With this review, we want to provide an update state of art relating the role of air pollution, in particular PM2.5, PM10 and NO2, in COVID-19 spread and lethality. The Authors, who first investigated this association, often used different research methods or not all include confounding factors whenever possible. In addition, to date incidence data are underestimated in all countries and to a lesser extent also mortality data. For this reason, the cases included in the reviewed studies cannot be considered conclusive. Although it determines important limitations for direct comparison of results, and more studies are needed to strengthen scientific evidences and support firm conclusions, major findings are consistent, highlighting the important contribution of PM2.5 and NO2 as triggering of the COVID-19 spread and lethality, and with a less extent also PM10, although the potential effect of airborne virus exposure it has not been still demonstrated.